Nursing care for infants: «el Hospital del Niño Jesús» - Francisca Casas Martínez; Teresa Ruiz Ureña; Begoña Carbelo Baquero; María Teresa Miralles Sangro; Marta Romero Llort (Universidad de Alicante, 1998)
The historical scenario in which the Hospital Pediátrico del Niño Jesús was created is analyzed in the present paper, as well as the evolution undertaken in nursing attention to infants.